Design of a Community-based Live-In Information System in Indonesia - Evi Maria (SCOPUS ID: 57093633500); Hanna Prillysca Chernovita; Sekar Widhiyaningrum; Irene Puspa Adventien (Universitas Islam Indragiri, 2026)
The development of information systems in the tourism sector is generally based on the assumption of a centralized business structure, with a single management unit and a unified financial recording mechanism. However, this assumption does not fully align with the characteristics of community-based tourism services, including live-in tourism, which are collectively managed by multiple autonomous actors. This study aims to design a conceptual model of a community-based live-in information system that aligns with the collective work structure and the distributed economic service recording mechanisms. The research employs an information system design approach through workflow analysis, field observations, and semi-structured interviews with key live-in operators in villages on the slopes of Mount Merbabu. The design focuses on modeling the work structure, service process flows, and cross-actor transaction recording mechanisms. Model validation was conducted by assessing the representational fidelity, process congruence, and recording coherence of the model as judged by internal community actors. The results indicate that the conceptual model effectively represents the distributed work practices of live-in services without imposing centralized organizational assumptions. This study contributes to the development of information system designs that prioritize representational alignment with community work practices rather than technical implementation or full automation of service processes.